Ecofeminism and rhetoric : critical perspectives on sex, technology, and discourse - Vakoch, Douglas A. (Berghahn Books, 2011)
By drawing on the complex interplay of ecology and feminism, ecofeminists identify links between the domination of nature and the oppression of women. This volume introduces a variety of innovative approaches for advancing ecofeminist activism, demonstrating how words exert power in the world. Contributors explore the interconnections between the dualisms of nature/culture and masculine/feminine, providing new insights into sex and technology through such wide-ranging topics as canine reproduction, orangutan motherhood and energy conservation. Ecofeminist rhetorics of care address environmenta.